(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
We update critical reviews of sites bearing hominin remains and/or tools from Europe (including the Balkans and Greece) and conclude that the only compelling evidence of hominin presence in these regions was after 0.9 Ma (million-years-ago), bracketed by the end of the Jaramillo subchron (0.99 Ma) and the Brunhes-Matuyama boundary (0.78 Ma) and straddling the climatic late Early Pleistocene revolution (EPR) at the onset of enhanced glacial/interglacial activity that reverberated worldwide. Europe may have become initially populated during the EPR when, possibly for the first time in the Pleistocene, vast and exploitable ecosystems were generated along the Danube-Po Gateway. These newly formed settings, characterized by lowlands with open grasslands and reduced woody cover during glacial/interglacial transitions, represented the closest analogues to the savanna environment to which several large mammals linked with hominins in a common food web were adapted. It was only after stable and vast grassland-savanna environments opened that large mammals (e.g. megaherbivores) could expand into Europe along the Danube-Po Gateway in conjunction with the attached food web to which hominins belonged.